A transdiagnostic approach to understanding eating disorders. - Wade, T; Bergin, J; Martin, N; Gillespie, N; Fairburn, C (2006)
Categorical models dominate the eating disorder field, but the tandem use of categorical and dimensional models has been proposed. A transdiagnostic dimensional model, number of lifetime eating disorder behaviors (LEDB), was examined with respect to (1) its relationship to a variety of indicators of the individual's functioning, (2) the degree to which it was influenced by genetic and environmental risk factors, and (3) exposure to specific environmental risk factors. Data from self-report and interview from 1002 female twins (mean age = 34.91 years, SD = 2.09) were examined. While 15.4% women met criteria for a lifetime eating disorder, 29% had at least one LEDB. The dimensional measure provided an indicator of associated functioning, and was influenced primarily by the nonshared environment. The number of LEDB was associated with the degree of impaired functioning. This impairment was associated with conflict between parents and criticism from parents when growing up.